Histological study of the Isotretinoin drug effect on the intrauterine prenatal development in the pregnant mice - Salih, Lina A. (Iraqi Journal of Science, 2021)
The isotretinoin drug is 13-cis-retinoic acid, is the treatment of severe acne and some skin cancers and used for dermatological conditions, this study was designed to detect the toxic role of the isotretinoin on the intrauterine development after implantation in albino mice during pregnancy. There are very little studies which indicating the side-effect of this drug on intra-uterine growth, so in the present research we tried to study the toxic effect of isotretinoin on the endometrial changes of uterus during the 2nd. and 3rd. trimester of gestation in pregnant mice after treatment with single chronic dose of the Isotretinoin drug (20 mg/B.wt) from first day of gestation until 21 days the last day of gestation.The present study examination of the uterus during the particular gestational days were perceived some fault in the endometrium tissue of the uterus since the hyperplasia of the lining epithelium of the uterus and thickening of the endometrium because of propagation of the endometrial glands and stroma and widening of the endometrial cavity in both control and treated groups of pregnant mice after the 7 day of gestation, we found some morphological changes appear in the pregnant mothers like, more thickness skin and change color of the body fur from white to yellow-whitish color, and less physical active and drop in appetite.The morphological changes in the pregnant mice after treated with (20mg / kg B.wt), isotretinoin dose, appear a significant decrease (p≤0.05) in the body weight. The histological results show a decreased in the numbers of the papillary projects of the endometrial tissue and change with few in numbers of the endometrial glands and loss stroma with thickness of the lining epithelium and this may because the resorption of the embryos inside the uterus compared to the control group.The present study clearly determine that the effect of isotretinoin on the histopathology of the uterus through pregnancy cause toxic on the embryos and result in resorption and damage the implanted embryos at altered particular gestational days in mice, as a result isotretinoin should be taking with attention and avoided at first post-implantation phase of gestation.